INCREASING SHALLOT EXPORTS AS AN IMPLEMENTATION OF ECONOMIC RESILIENCE IN THE HORTICULTURAL SECTOR DURING THE COVID-19 PANDEMIC - Ashroniyah Fella (UNIDA GONTOR, 2022)
This study explains the increasing of shallot exports as a form of horticultural economic resilience during the Covid-19 pandemic. Shallots are exported to several countries such as Thailand, Singapore, Malaysia, Japan, Vietnam, and Saudi Arabia. This research uses a qualitative method to see the analysis of economic resilience through the horticultural sector, namely shallots in improving the country's economy. To answer and complete this research, researchers also use two important concepts, namely, economic resilience as instrument to measure the effect of shallot exports on Indonesia's horticultural economic resilience during the covid-19 pandemic and the concept of competitive advantage to analyze excellence in business, where export activities can increase Indonesia's horticultural economic resilience. This study found that Indonesia increased shallot exports to many countries by encarging trade cooperation. It because Indonesia has high quality standards for shallot commodities through supporting natural and human resources. By using a qualitative explanatory method, this can be proven by an increase in demand for shallot exports and more cooperation with importing countries, especially, Thailand, Singapore, and Vietnam. Thus causing an increase in Indonesia's GDP during the Covid-19 pandemic. Keywords: increasing exports, shallots, horticultural economic resilience.